Lack of Contribution of p66shc and Its Mitochondrial Translocation to Ischemia-Reperfusion Injury and Cardioprotection by Ischemic Preconditioning - Boengler, Kerstin; Bencsik, Péter; Palóczi, János; Kiss, Krisztina; Pipicz, Márton; Pipis, Judit; Ferdinandy, Péter; Schlüter, Klaus-Dieter; Schulz, Rainer (Frontiers in Physiology, 2017)
Whereas high amounts of reactive oxygen species (ROS) contribute to cardiac damage following ischemia and reperfusion (IR), low amounts function as trigger molecules in the cardioprotection by ischemic preconditioning (IPC). The mitochondrial translocation and contribution of the hydrogen peroxide-generating protein p66shc in the cardioprotection by IPC is unclear yet. In the present study, we investigated the mitochondrial translocation of p66shc, addressed the impact of p66shc on ROS formation after IR, and characterized the role of p66shc in IR injury per se and in the cardioprotection by IPC. The amount of p66shc in subsarcolemmal (SSM) and interfibrillar mitochondria (IFM) isolated from wildtype mouse left ventricles (LV) was determined after 40 min normoxic perfusion and after 30 min ischemia and 10 min reperfusion (IR) without and with IPC. The p66shc content in SSM (in % of normoxic controls, n=5) was 174±16% (n=6, p<0.05) after IR, and was reduced to 128±13% after IPC (n=6, p=ns). In IFM, the amount of p66shc remained unchanged (IR: 81±7%, n=6; IPC: 110±5%, n=6, p=ns). IR induced an increase in ROS formation in SSM and IFM isolated from mouse wildtype LV, which was more pronounced in SSM than in IFM (1.18±0.18 vs 0.81±0.16, n=6, p<0.05). In mitochondria from p66shc-knockout mice (p66shc-KO), the increase in ROS formation by IR was not different between SSM and IFM (0.90±0.11 vs. 0.73±0.08, n=6, p=ns). Infarct size (in % of the left ventricle) was 51.7±2.9% in wildtype and 59.7±3.8% in p66shc-KO hearts in vitro and was significantly reduced to 35.8±4.4% (wildtype) and 34.7±5.6% (p66shc-KO) hearts by IPC, respectively. In vivo, infarct size was 57.8±2.9% following IR (n=9) and was reduced to 40.3±3.5% by IPC (n=11, p<0.05) in wildtype mice. In p66shc-knockout mice, infarct sizes were similar to those measured in wildtype animals (IR: 56.2±4.3%, n=11; IPC: 42.1±3.9%, n=13, p<0.05). Taken together, the mitochondrial translocation of p66shc following IR and IPC differs between mitochondrial populations. However, similar infarct sizes after IR and preserved infarct size reductions by IPC in p66shc-KO mice suggest that p66shc-derived ROS are not involved in the cardioprotection by IPC nor do they contribute to IR injury per se.